2017
DOI: 10.1007/s40071-017-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic study in hepatopancreas of Litopenaeus vannamei response to white spot syndrome virus

Abstract: White spot syndrome virus (WSSV) cause great harm in shrimp aquaculture. To understand the impact of viral infection on the shrimp metabolism, we monitored the culture farms of Litopenaeus vannamei and collected the samples on different stages of WSSV infection. The hepatopancreas of shrimp were separated, and then used gas chromatography mass spectrometry to detect the metabolites. Through the mass spectrometric analysis combined with multivariate data analysis, including PCA and OPLS models, metabolism of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Interestingly, isoleucine, methionine, tyrosine, and phenylalanine levels exhibited a significant increase at 72 hpi and then dramatically decreased at 144 hpi (Figure 4). Similar results were reported by Wu et al [38], who found that amino acid levels were increased after WSSV-infection and decreased when the shrimp was close to death. However, more research is needed to further elucidate this mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, isoleucine, methionine, tyrosine, and phenylalanine levels exhibited a significant increase at 72 hpi and then dramatically decreased at 144 hpi (Figure 4). Similar results were reported by Wu et al [38], who found that amino acid levels were increased after WSSV-infection and decreased when the shrimp was close to death. However, more research is needed to further elucidate this mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…The decreasing trend in lactate levels from 72 to 144 hpi indicates that lactate contributes to the gluconeogenic supply of glucose for energy requirement in infected shrimp [27]. Wu et al [38] reported that decreased glucose and lactate levels during the late phase of infection increases in gluconeogenesis in the hepatopancreas of shrimp. In addition, the nucleotide metabolism also exhibited unique changes in the hepatopancreas from 72 to 144 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…37 In the hepatopancreas of WSSV-infected shrimp, there were increases in glycolysis, the TCA cycle and amino acid metabolites during the early stages of WSSV infection, whereas at later stages, metabolite concentrations were similar to those in uninfected control shrimp. 67 In a transcriptomic analysis of WSSVinfected shrimp haemocytes, that focused on the early activation of the neuro-endocrine immune system there was upregulation of the transamination enzyme alanine transaminase (ALAT) at 6 hpi. This enzyme catalyses the conversion of glutamate to α-KG, and could thus provide a mechanism by which glutamate replenishes the TCA cycle and promotes WSSV replication.…”
Section: Tca Cycle and Glutamine Metabolismmentioning
confidence: 99%
“…54 During the early stages of WSSV infection of penaeid shrimp (P. japonicus), increased intestinal linoleic acid levels 55 and other metabolites in the hepatopancreas 53,56,57 or increased glucose 56,57 and lactate levels in the hepatopancreas 53,56,57 were found, whereas at later stages of the infection, decreased glucose and lactate levels but increased glycine levels were found. 57 Analysis of hepatopancreatic transcriptome data of Taura syndrome virus (TSV)-infected P. vannamei revealed many differentially expressed genes involved in metabolic process and mainly have antiviral, antibacterial, protease, protease inhibitor, signal transduction and transcription factor, cell death and cell adhesion functions, 58 which could interfere with the integrity or metabolism of microorganisms. Similarly, in IHHNV-infected P. vannamei, significantly dysregulated metabolites such as glucose, lactic acid, triacylglycerides and cholesterol were found in the plasma and hepatopancreas, suggesting that the virus modulates host metabolic pathways to maximize the use of these metabolites for replication.…”
Section: Viral-induced Metabolic Changes In Crustaceansmentioning
confidence: 99%
“…In crustaceans, especially shrimp, changes in many metabolites, especially, amino acid metabolites 53,56,57 and lipids, 53,56 could be used as metabolic biomarkers during viral infections.…”
Section: Viral-induced Metabolic Changes In Crustaceansmentioning
confidence: 99%